A CORPUS-BASED ANALYSIS OF FIRST-PERSON PRONOUN IN NIKI’S SONG - Mukminin, Muhamad Saiful; Fitri, Fajriani; Atikoh, Iklilah; Yaman, Nurinsani (Teaching English as Foreign Language, Literature and Linguisticss, 2024)
This study aims to analyze the use of first-person pronouns in NIKI's song lyrics, focusing on their frequency, pattern, and context of usage. The research employs a descriptive qualitative-quantitative approach, combining corpus analysis with contextual interpretation. The data consists of song lyrics from NIKI's albums and popular tracks, formatted into a compatible text file (.txt) for analysis using AntConc software version 4.3.1. Data collection involved gathering lyrics from reliable sources, cleaning the data, and preparing it for analysis. The analysis process included identifying the frequency of first-person pronouns, observing distribution patterns through the concordance feature, and interpreting the context and meanings of pronoun usage. The findings reveal a dominance of the pronoun "I" (589 occurrences) over "We" (138 occurrences), indicating a focus on individual experiences and emotions in NIKI's lyrics. The study identifies various patterns, including "I + to be," which reflects deep emotional states, self-reflection, and regret; "I + modal," which conveys feelings and desires; and "I + verb," which directly expresses actions and emotions. Additionally, the "We" patterns, such as "We + To Be" and "We + Modal," illustrate collective experiences, possibilities, and relationship dynamics. The results highlight the contrasting roles of individual and collective perspectives in NIKI’s songwriting, enriching the emotional depth of her lyrics.